HUBUNGAN ANTARA PEMBANGUNAN INFRASTRUKTUR DAN KEMAMPUAN USAHA MASYARAKAT - Nanang Bagus Srihardjono (REFORMASI, 2019)
The purpose of this study was to find out how the relationship between infrastructure development and community skills in the village of SuruhTembawang, EntikongSub-district, Sanggau District. The method used in this study was descriptive quantitative. The sample technique applied was a purposive sampling with a sample of 100 people. The data collection techniques invloved questionnaire and documentation. The sata analysis used regression, validity test, reliability test, correlation test. The results of the studyshowed that there was a strong relationship between infrastructure development and the community business capacity increasingat poin of 0.770 (77%). While the direction of the relationship was positive because the value of r was also positive.It meant that a better infrastructuredevelopment affected the improvement of business capacity of the community in SuruhTembawangvillage.